Health Professional–Identified Barriers to Living Donor Kidney Transplantation: A Qualitative Study - Shaifali Sandal; Kathleen Charlebois; Julio F. Fiore; David Kenneth Wright; Marie-Chantal Fortin; Liane S. Feldman; Ahsan Alam; Catherine Weber (Canadian Journal of Kidney Health and Disease, 2019)
Background: Living donor kidney transplantation (LDKT) has several advantages over deceased donor kidney transplantation. Yet rates of living donation are declining in Canada and there exists significant interprovincial variability. Efforts to improve living donation tend to focus on the patient and barriers identified at their level, such as not knowing how to ask for a kidney or lack of education. These efforts favor those who have the means and the support to find living donors. Thus, a Canadian Institutes of Health Research (CIHR)-organized workshop recommended that education efforts to understand and remove barriers should focus on health professionals (HPs). Despite this, little attention has been paid to what they identify as barriers to discussing LDKT with their patients. Objective: Our aim was to explore HP-identified barriers to discuss living donation with patients in 3 provinces of Canada with low (Quebec), moderate (Ontario), and high (British Columbia) rates of LDKT. Design: This study consists of an interpretive descriptive approach as it enables to move beyond description and inform clinical practice. Setting: Purposive criterion and quota sampling were used to recruit HPs from Quebec, Ontario, and British Columbia who are involved in the care of patients with kidney disease and/or with transplant coordination. Patients: Not applicable. Measurements: Semistructured interviews were conducted. The interview guide was developed based on a preliminary analytical framework and a review of the literature. Methods: Thematic analysis was used to analyze the data stemming from the interviews. The coding process comprised of a deductive and inductive approach, and the use of a qualitative analysis software (NVivo 11). Following this, themes were identified and developed. Interviews were conducted until thematic saturation was obtained. In total, we conducted 16 telephone interviews as thematic saturation was attained. Results: Six predominant themes emerged: (1) lack of communication between transplant and dialysis teams, (2) absence of referral guidelines, (3) role perception and lack of multidisciplinary involvement, (4) HP’s lack of information and training, (5) negative attitudes of some HP toward LDKT, (6) patient-level barriers as defined by the HP. HPs did mention patients’ attitudes and some characteristics as the main barriers to discussions about living donation; this was noted in all provinces. HPs from Ontario and British Columbia indicated multiple strategies being implemented to address some of these barriers. Those from Ontario mentioned strategies that center on the core principles of provincial-level standardization, while those from British Columbia center on engaging the entire multidisciplinary team and improved role perception. We noted a dearth of such efforts in Quebec; however, efforts around education and promotion, while tentative, have emerged. Limitations: Social desirability and selection bias. Our analysis might not be applicable to other provinces. Conclusions: HPs involved with the referral and coordination of transplantation play a major role in access to LDKT. We have identified challenges they face when discussing living donation with their patients that warrant further assessment and research to inform policy change.